Computational fluid dynamics (CFD) simulation of flow in mixing reactor - Chong, Wain Ket (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Mixing reactor is a common unit operation in many industrial processes. It is often encountered multiphase flow for mixing process. A computational fluid dynamics (CFD) model based on the mixture formulation for multiphase flow was created to study the mixing hydrodynamics of oil and water in a mixing reactor. This project aimed to develop a reliable CFD model that was able to predict the hydrodynamic properties like velocity or volume fraction. A grid dependency study was conducted to determine the effect of coarse, medium and fine meshes. The simulations were based on an experimental study where the mixing of oil and water occurred in the external loop. It had shown that the medium mesh was seem satisfactory to fulfill the evaluation criterion. The error between prediction of CFD model and experimental data was also within the tolerant range.